PENGEMBANGAN MEDIA AUDIO VISUAL PELATIHAN MEDITASI UNTUK REMAJA BUDDHIS DI VIHARA AMRTA - Yanti, Dwi; Budiyono, Herman; Emosda, Emosda (Program Magister Teknologi Pendidikan Universitas Jambi, 2014)
Development of audio-visual media meditation training specifically designed for the needs meditation. This medium contains stages in meditation so easily understood and followed by meditation trainees. The development of audio-visual media conducted by researchers carried out by adapting the model of ( Research and Development / R & D ). The method consists of 10 ( ten ) steps , namely ( 1 ) the potential and problems , ( 2 ) collection of data , ( 3 ) product design , ( 4 ) validation of the design , ( 5 ) revision of the design , ( 6 ) test products , ( 7 ) revision of the product , ( 8 ) utility testing , ( 9 ) the revision of the product , ( 10 ) mass production, but for mass production, the researchers do not do this in accordance with the restrictions on the problem. Keyword: audio-visual media, meditation training, development